Loss to follow-up: initial non-responders do not differ from responders in terms of 2-year outcome in a hip arthroscopy registry. Issue 2 (6th August 2020) - Lindman, Ida; Olsson, Harald; Öhlin, Axel; Hamrin Senorski, Eric; Stålman, Anders; Ayeni, Olufemi R; Sansone, Mikael
Abstract: Loss to follow-up in registry studies is a problem due to potential selection bias. There is no consensus on the effect of response rate. The aim of this study was to compare patient-reported outcome measures (PROMs) between responders and initial non-responders (INR) in a hip arthroscopy registry and to examine whether demographics affect the response rate. Data from hip arthroscopies performed at two centres in Gothenburg were collected and the patients were followed up with PROMs. The follow-up was a minimum of 2 years after surgery. All 536 patients who underwent primary hip arthroscopies during 2015 and 2016 and had recorded pre-operative PROMs were included. A total of 396 patients completed the follow-up and were labelled 'Responders' (R) and 107 patients responded after reminders were sent and labelled 'Initial non-responders' (INR). The mean time of follow-up was 24.7 ± 2.9 and 42.5 ± 7.0 months for the R- and INR-group, respectively. There were no differences between the two groups at the follow-up for the Copenhagen Hip and Groin Outcome Score, European Quality of life 5 dimensions questionnaire, EQ-VAS, International Hip Outcome Tool or a visual analogue scale for hip function. A larger proportion of R was satisfied after hip arthroscopy compared with INR (86% versus 70%, P = 0.0003). INR were younger than responders (31.5 ± 12.5 versus 35.6 ± 12.7 years of age). The conclusion of the study was that there were no differences between R and INR at the follow-up across the PROMs except patient satisfaction, where responders were more satisfied.